PENINGKATAN KUALITAS PRODUK INDUSTRI RUMAH TANGGA BLACK GARLIC MELALUI ALAT FERMENTASI EFISIEN DAN KEMASAN MODERN - Dandun Mahesa Prabowoputra; Gunawan Prasetyo; Muhammad Pasha; Akhlis Rahman Sari Nurhidayat; Bhre Wangsa Lenggana; Ameliyana Rizky Syamara Putri Akhmad Yani (Universitas Mataram, 2026)
Home industries play a strategic role in supporting local economic growth and community empowerment. One of the leading products from these industries is black garlic, known for its high health benefits. However, the quality of black garlic products from these industries is often suboptimal due to limited efficient fermentation technology and a lack of modern packaging that can attract market interest. Therefore, this program is designed to improve the quality of black garlic products through the development of efficient fermentation equipment and the implementation of modern packaging. The main objective of this program is to increase production capacity, quality consistency, and the competitiveness of black garlic products from these industries, with aspects of aesthetics, functionality, and clear product information, such as health benefits and natural production processes. Training is provided to home business owners to improve their skills in operating new fermentation equipment and adopting modern packaging techniques. The mentoring activities include training in digital marketing strategies, social media, and packaging design. The program's outcomes include increased production process efficiency, consistent black garlic quality, and product added value through modern packaging. The expected long-term impact is increased household income, market expansion, and a strengthened position of the home industry in the local economy. With an approach focused on integrating simple technology, design innovation, and marketing strategies, this program supports the sustainability of home industries based on local wisdom. Through this program, it is hoped that synergy will be created between business actors, academics, and the government to strengthen an innovative and highly competitive home industry ecosystem, while simultaneously making a tangible contribution to sustainable local economic development.